Gonadal involvment in leprosy — study of gynaecomastia, testicular and epididymal involvement and therapeutic efficacy of indigenous drugs - MIGAM, Pranesh (1984)
Sixty male patients of leprosy (mean age = 27.2+5.04 years) selected at random, were studied for gonadal involvement and therapeutic efficacy of two indigenous drugs. Of these 34 were married, with the mean duration of illness 4.17+3.27 years. Only those with lepromatous and dimorphous leprosy developed testicular and epididymal changes. Testicular pain and/or swelling (lepromatous =62.5%, dimorphous 30%) was the commonest presenting feature. Altered sexual function was observed in 34 (56.6%) cases, while 11 patients revealed altered sexual hair pattern and nine gynaeco-mastia. Reduced testicular size associated with soft feel was present in 25% of cases with no testicular sensation in 8 (13.3%) and impaired testicular sensation in 9 (15%) patients. Spermogram revealed azoospermia in 19 (35%) and oligospermia in 16 (26.6%) patients. Histopathological findings of testicle biopsy revealed evidence of leprous pathology irrespective of testicular size, semen picture and clinical manifestations. Histopatho-logical changes had shown marked variation and so did not enable categorising them into vascular, interstitial and obliterative phases. These changes were believed to be due to the altered gonadal state in leprosy. The therapeutic efficacy of the indigenous preparations, Speman and Tentex forte (Himalaya) was evaluated subjectively as well as objectively in 34 patients. 823% of cases showed subjective improvement while objective improvement in spermogram was noted in 87.5% cases with oligospermia. The drugs have no side effect and were well tolerated.